Analisis Pengaruh Atribut Terhadap Keputusan Pembelian Roti Soek Padjadjaran Bogor - Doni Sahat Tua Manalu; Vela Rostwentivaivi; Gina Jaudah; Chintya Eka Putri; Azrina Qisthina Zamila; Riza Muharmayenti; Fauzan Ariq (CV. KAMPUSA AKADEMIK PUBLISING, 2024)
Bread is a staple food for people abroad. However, as time progressed, Indonesian people began to make bread one of the staple foods that was consumed quite often. This research data uses qualitative and quantitative methods with primary and secondary data collection which is processed using fishbein analysis and multiple linear regression. The aim of this research is to determine the significant level of influence of the attributes of taste, aroma, texture, price, packaging design, product durability, product availability, service and cleanliness of the place on purchasing Roti Soek Padjadjaran products. Fishbein's analysis shows that the attributes of taste, price, product durability and service are the attributes with the four highest ratings. Multiple linear analysis shows the results that the taste and service attributes are the attributes that have a significant positive influence as variables that influence purchasing decisions for Soek Padjajaran Roti using a confidence level of 95 percent.